Evaluation of the antibacterial activity of essential oils from oregano (Origanum vulgare) against Escherichia coli strains isolated from meat products - L. Brito-Junior; H. C. Brito; M. M. Simões; B. Santos; F. M. C. Marques; M. A. A. Medeiros; M. S. Alves; J. H. A. Farias; C. T. Pereira; A. F. Diniz; A. A. Oliveira-Filho; V. L. R. Vilela (Brazilian Journal of Biology)
Abstract The objective of this study was to analyze the antimicrobial and anti-stick capacity of essential oil extracted from oregano (Origanum vulgare) in relation to various strains of Escherichia coli (Ec 41, Ec 42, Ec 44, Ec 45) isolated from meat products. Techniques such as Determination of Minimum Inhibitory Concentration were used (MIC) and Minimum Bactericidal Concentration (CBM). Furthermore, the method was used disk diffusion method to examine the interaction between O. vulgare essential oil and synthetic antibiotics. Determination of the Inhibitory Concentration was also carried out Minimum Adhesion (CIMA). The results indicated that O. vulgare oil demonstrated antimicrobial activity against the E. coli strains tested, with values of MIC ranging between 256 μg/mL and 512 μg/mL, and MBC values ranging between 256 μg/mL and 1.024 μg/mL. Regarding associations, it was observed that O. vulgare had an antagonistic effect towards certain antibiotics, mainly ampicillin, showing greater interference from the essential oil. Furthermore, the oil was effective in inhibiting the adherence of E. coli bacterial strains, demonstrating a more significant antibiofilm agent than 0.12% chlorhexidine digluconate, a commonly used antibacterial. In short, O. vulgare essential oil exhibited antimicrobial potential against E. coli strains isolated from meat products, suggesting which, upon more detailed investigations, could be used both in isolation or in combination with synthetic antibiotics to combat infections caused by this pathogen.